PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Lolo Lembang, Sani; Mariani Manik, Yuni; Rusno (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2025)
Many companies pay little attention to the Occupational Health and Safety (K3) of their employees, which can cause work accidents and health problems. This can be overcome by implementing an Occupational Safety and Health (K3) program. By creating safe and comfortable working conditions, companies can achieve quality employee performance. If these two aspects are implemented properly, employees will feel satisfied. This study aims to examine and analyze the effect of K3 on employee performance, the influence of the work environment on employee performance, the role of job satisfaction in mediating the effect of K3 on employee performance, and the role of job satisfaction in mediating the influence of the work environment on employee performance. This study uses a quantitative method with an explanatory research approach. The population of this research is the employees of staff Dinas Tenaga kerja bagian kelistrikan Kabupaten Puncak Jaya. Data collection techniques used are questionnaires, interviews, and observation. The sample for this research was taken by purposive sampling, amounting to 100 manufacturing employees of staff Dinas Tenaga kerja bagian kelistrikan Kabupaten Puncak Jaya. Data analysis technique uses Partial Least Square. The variables studied were Occupational Health and Safety (K3) (X1), Work Environment (X2), Employee Performance (Y), Job Satisfaction (Z). The results of this study indicate that Occupational Health and Safety (K3) influences employee performance, work environment influences employee performance, job satisfaction mediates the effect of Occupational Health and Safety (K3) on employee performance, and job satisfaction mediates the effect of work environment on employee performance.